Skema Pertahanan dalam Kondisi Kontingensi N-2 Saluran Pemalang-Ungaran dan Depok-Tasikmalaya - kevin rachman firdaus; Hadi Suyono; Tri Nurwati; Rini Nur Hasanah (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2021)
A fault of transmission lines in the process of transmitting electricity has a huge impact. One of the impacts of the disruption in August 2019 on the island of Java was the partial blackout in the Java-Bali electricity system due to contingency of the 500 kV Pemalang-Ungaran and Depok-Tasikmalaya transmission lines. Prevention of partial blackouts is required by devising defense schemes that can compensate for the impact of these contingency events. Defense schemes can be done by doing load shedding and generator tripping. Both methods are able to evacuate a large amount of power in a relatively fast time, so that it can improve the frequency value in a short time. The system frequency response has experienced recovery with an increase in frequency in the West Java Island and a decrease in the frequency in the East Java Island. The result of load shedding is the disconnection of 6 load buses in 5 main stages of the system and the result of generator tripping is the disconnection of 2-unit generators in 2 stages of the system.